FORTIFIKASI I ODIUM DALAM GULA KELAPA DAN KESTABILAN'NYA DALAM PROD UK PANGAN - Rumpoko Wicaksono; Rifda Naufalin; Hidayah Dwiyanti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
Iodine fortification of brown sugar is an effort to improve variation ofiodized foods in preventing iodine deficiency disorders in Indonesia. This research aimed to: a) study the effect of fortification time(iodine addition) in iodized brown sugar processing on iodine retention in product; b) deter• mine the source ofiodine that suitable for iodine fortification ofbrown sugar; c) study the packaging type that can retain iodine stability of iodized brown sugar during storage; d) study the effect of iodized brown sugar usage in making of"kecap" (soy sauce) and "bumbu pecel" on product accep• tance according to sensory perception; e) study the effect of shelflife on iodine stability of'iodized "kecap" and "bumbu pecel". Results of this research showed that: a) fortifican (iodine) addition at 115 c cooking temperature produced iodized brown sugar with iodine-content higher than at cooking temperature of 11 O "C; b) stability ofKJ03 is better than Kl; c) polypropilene combined with silica gel or aluminum foil can be used as packaging material to retain iodine-content during storage; d) the use of iodized brown sugar in "kecap'' and "bum bu pecel" accepted by consumers sensorically; e) iodine stability in "burnbu pecel" is better than in "kecap". During three weeks storages, the decrease of iodine• content of"bumbu pecel" iodized with Kl is 36.46 percents, and that iodized with K103 is 11.14 percents. Furthermore, for "kecap'', the iodine-content decrease are 68.89 and 50.23 percents, respectively in "kecap" iodized with Kl and KlOr